A positioning light-transmitting ceramic plate and a preparation method thereof
By inkjet printing finely engraved ink patterns on the translucent ceramic plate and applying surface glaze and glaze, the problem of insufficient fine texture of the existing ceramic plate pattern is solved, and the local high-transparency effect is achieved, which improves the decoration of the ceramic plate Effects and application space.
Patent Information
- Application Number
- CN202411336967.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-09-25
AI Technical Summary
The existing translucent ceramic plates are not detailed and profound enough in the pattern texture, resulting in insufficient decorative effects and unable to fully demonstrate the specific light transmission effect of the ceramic plates.
By adopting the preparation method of positioning translucent ceramic plate, the finely engraved ink pattern is printed on the translucent blank, the surface glaze and glaze are applied, and polished after firing at high temperature, the local high-translucent effect is achieved and the stone texture is formed. Pattern decoration.
It improves the decorative effect and visual effect of ceramic plates, broadens the application space of architectural ceramic products, and achieves richer light transmission through local high light transmission, enhancing the decorative value of ceramic plates.
Smart Images

Figure CN118851802B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a positioning light-transmitting ceramic plate and a preparation method thereof, belonging to the technical field of ceramic tile production and manufacturing. Background Art
[0002] Under the irradiation of artistic lighting or natural light, the positioned translucent ceramic plate transmits light from a specific position of the ceramic plate, giving people a hazy, jade-like, exquisite and translucent feeling, which can fully display the pattern color, texture and texture of the translucent ceramic plate, greatly improving the visual effect and decorative effect of the ceramic plate. However, most of the existing translucent ceramic plate products present a full-body translucent effect, and only use inkjet patterns for surface decoration, and the depiction of the pattern texture is not detailed and profound enough. Summary of the invention
[0003] In response to the above problems, the present invention provides a positioned translucent ceramic plate and a preparation method thereof, which can achieve local high light transmittance at specific positions of the throughout translucent ceramic plate, and can be used to produce large translucent ceramic plates decorated with stone texture patterns, thereby improving the decorative effect of the ceramic plates and broadening the application space of building ceramic products.
[0004] In a first aspect, the present invention provides a method for preparing a positioning light-transmitting ceramic plate. The preparation method comprises the following steps:
[0005] Inkjet printing of finely carved ink patterns on the surface of the light-transmitting blank;
[0006] Applying a top glaze to the surface of the blank after the inkjet printing of the finely carved ink pattern;
[0007] Inkjet printing a common ink pattern on the surface of the blank after the top glaze is applied;
[0008] Applying glaze to the surface of the blank after the ordinary ink pattern is inkjet printed;
[0009] The green body with glaze applied is fired and polished to obtain the positioning light-transmitting ceramic plate.
[0010] Preferably, the mineral composition of the light-transmitting blank includes: by mass percentage, 10-15% of water-ground potassium sodium sand, 5-10% of water-ground potassium feldspar, 5-10% of burned talc, 10-15% of wollastonite, 30-40% of ultra-white kaolin, and 20-30% of high-calcium and high-aluminum frit; wherein the chemical composition of the high-calcium and high-aluminum frit includes: by mass percentage, SiO 2 :40~45%,Al 2 O 3 : 20~30%, CaO: 10~15%, MgO: 1~5%, K 2 O: 1~5%, Na 2 O: 1~5%.
[0011] Preferably, the chemical composition of the light-transmitting blank includes: in terms of mass percentage, burning loss: 2-5%, SiO 2 :55~60%,Al 2 O 3 :16~23%,Fe 2 O 3 :0.5% or less, TiO 2 : less than 0.3%, CaO: 5~10%, MgO: 1~5%, K 2 O: 1~5%, Na 2 O: 1~5%.
[0012] Preferably, the mineral composition of the glaze includes, by mass percentage, 30-35% of water-ground potassium sodium sand, 20-25% of water-ground potassium feldspar, 10-15% of calcined alumina, 5-10% of zirconium silicate, and 25-30% of ultra-white kaolin.
[0013] Preferably, the chemical composition of the glaze includes: by mass percentage, loss on ignition: 2-5%, SiO 2 :58~65%,Al 2 O 3 :23~28%,Fe 2 O 3 :0.3% or less, TiO 2 :0.2% or less, K 2 O: 2~5%, Na 2 O: 2~6%, ZrO 2 :3~6%.
[0014] Preferably, the glaze is applied by spraying; the specific gravity of the glaze is 1.40-1.45 g / cm 3 , glaze application amount is 550~650g / m 2 .
[0015] Preferably, the mineral composition of the polishing glaze includes, by mass percentage, 10-15% potassium feldspar, 5-10% kaolin, 5-10% quartz, 5-10% calcined kaolin, 20-30% high calcium high aluminum frit, 10-15% burned talc, 15-20% wollastonite, and 3-6% zinc oxide; wherein the chemical composition of the high calcium high aluminum frit includes, by mass percentage, SiO 2 :40~45%,Al 2 O 3 : 20~30%, CaO: 10~15%, MgO: 1~5%, K 2 O: 1~5%, Na 2 O: 1~5%.
[0016] Preferably, the chemical composition of the polishing glaze includes: by mass percentage, loss on burning: 1-5%, SiO 2 :50~55%,Al 2 O 3 :15~20%,Fe 2 O 3 :0.3% or less, TiO 2 : 0.2% or less, CaO: 10~15%, MgO: 5~10%, K 2 O: 1~5%, Na 2 O: 1~5%, ZnO: 3~6%.
[0017] Preferably, the glaze is applied by spraying; the specific gravity of the glaze is 1.50-1.55 g / cm 3 , glaze application amount is 500~550g / m 2 .
[0018] Preferably, the firing temperature is 1180-1220° C., and the firing period is 60-80 minutes.
[0019] In a second aspect, the present invention provides a positioning light-transmitting ceramic plate. The positioning light-transmitting ceramic plate is obtained according to the preparation method.
[0020] Beneficial Effects
[0021] The present invention can achieve local high light transmittance at specific positions of the entire light-transmitting ceramic plate, and can be used to produce large light-transmitting ceramic plates decorated with stone texture patterns, thereby improving the decorative effect of the ceramic plates and broadening the application space of architectural ceramic products. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The light-transmitting effect diagram of the light-transmitting ceramic plate under the light, where the left picture is a light-transmitting ceramic plate without fine-engraving ink printing, and the right picture is a light-transmitting ceramic plate with fine-engraving ink patterns printed;
[0023] Figure 2 This is a brick surface effect diagram of the positioning light-transmitting ceramic plate of Example 1;
[0024] Figure 3 This is the brick surface effect diagram of Example 2;
[0025] Figure 4 This is the brick surface effect diagram of Example 3;
[0026] Figure 5 This is the brick surface effect diagram of Example 4;
[0027] Figure 6 This is the brick surface effect diagram of Example 5. DETAILED DESCRIPTION
[0028] The present invention is further described by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.
[0029] The present invention firstly inkjet prints a finely carved ink pattern imitating stone texture on a transparent blank, and then applies a glaze. The finely carved ink pattern can "peel off" the glaze at a specific position of the transparent ceramic plate to expose the blank to form a stone texture; then, the inkjet ordinary ink pattern is printed in sequence and a polishing glaze is applied. The polishing glaze can cover and level the texture formed by the finely carved ink on the surface of the ceramic plate; finally, firing and post-processing are performed to realize customized batch production of a series of transparent ceramic plate products. The following is an exemplary description of the preparation method of the positioning transparent ceramic plate of the present invention.
[0030] Prepare a light-transmitting body. In order not to affect the overall light-transmitting performance of the ceramic plate, the present invention develops a high-light-transmitting body formula. Even the glaze-covered part of the ceramic plate has excellent light-transmitting performance. Preferably, a light-transmitting body of a high-alkaline earth metal flux system is used. The mineral composition of the light-transmitting body includes, by mass percentage, 10-15% of water-ground potassium sodium sand, 5-10% of water-ground potassium feldspar, 5-10% of burned talc, 10-15% of wollastonite, 30-40% of ultra-white kaolin, and 20-30% of high-calcium and high-aluminum frit.
[0031] The chemical composition of the high calcium and high aluminum frit includes: SiO 2 :40~45%,Al 2 O 3 : 20~30%, CaO: 10~15%, MgO: 1~5%, K 2 O: 1~5%, Na 2 O: 1~5%.
[0032] In some embodiments, the mineral composition of the high calcium and high aluminum frit includes: by mass percentage, potassium feldspar 12%, sodium feldspar 14%, aluminum oxide 20%, calcined talc 13%, wollastonite 28%, and kaolin 13%. According to the mineral composition of the high calcium and high aluminum frit, the raw materials are weighed, mixed evenly, and melted at 1400-1500° C. for 2-3 hours to obtain glass liquid; the glass liquid is then water quenched and crushed to obtain a high calcium and high aluminum frit.
[0033] Weigh the raw materials according to the mineral composition of the light-transmitting green body, add water to ball-mill them evenly, spray powder to granulate them, and obtain the light-transmitting green body powder. The water content of the light-transmitting green body powder can be 7-8wt%.
[0034] The light-transmitting green body powder is pressed into a shape to obtain a light-transmitting green body. The molding method includes but is not limited to dry pressing molding. For example, dry pressing molding is performed by a press. The thickness of the light-transmitting green body can be 4 to 8 mm. For example, the thickness of the light-transmitting green body is about 6.2 mm.
[0035] In some embodiments, the chemical composition of the light-transmitting blank includes: in terms of mass percentage, burning loss: 2-5%, SiO 2 :55~60%,Al 2 O 3 :16~23%,Fe 2 O 3 :0.5% or less, TiO 2 : less than 0.3%, CaO: 5~10%, MgO: 1~5%, K 2 O: 1~5%, Na 2 O: 1-5%. As an example, the chemical composition of the light-transmitting blank includes: in terms of mass percentage, burning loss: 2-5%, SiO 2 :55~60%,Al 2 O 3 :16~23%,Fe 2 O 3 :0.01~0.5%, TiO 2 :0.01~0.3%, CaO: 5~10%, MgO: 1~5%, K 2 O: 1~5%, Na 2 O: 1~5%.
[0036] The light-transmitting green body is dried at high temperature.
[0037] The finely carved ink pattern is printed by inkjet printing on the surface of the dried transparent blank. The finely carved ink pattern can be accurately printed on the surface of the brick blank by a digital inkjet printer. Commercial finely carved ink can be used. In some technical solutions, the finely carved ink pattern is a finely carved ink pattern imitating the texture of stone. Figure 1 The light-transmitting effect of the light-transmitting ceramic plate under the light is shown in the figure below. The left figure is a light-transmitting ceramic plate without fine-engraving ink printing, and the right figure is a light-transmitting ceramic plate with fine-engraving ink patterns printed on it. It can be seen that the application of fine-engraving ink patterns is conducive to improving the positioning decoration effect.
[0038] After the inkjet printing of the finely carved ink pattern, the glaze is applied on the surface of the transparent body. Since the melting temperature of the glaze is high and the glass phase content in the glaze layer is very small, the glaze has a strong light blocking effect on the transparent ceramic plate, and the light transmittance of the area covered by the glaze is lower than that of the area not covered by the glaze.
[0039] The present invention designs a glaze formula that is compatible with a light-transmitting body. The mineral composition of the glaze includes: by mass percentage, 30-35% of water-ground potassium-sodium sand, 20-25% of water-ground potassium feldspar, 10-15% of calcined aluminum oxide, 5-10% of zirconium silicate, and 25-30% of ultra-white kaolin. As an example, the mineral composition of the glaze includes: by mass percentage, 30-35% of water-ground potassium-sodium sand, 20-25% of water-ground potassium feldspar, 10-13% of calcined aluminum oxide, 5-10% of zirconium silicate, and 25-30% of ultra-white kaolin.
[0040] In some embodiments, the chemical composition of the glaze includes: by mass percentage, loss on ignition: 2-5%, SiO 2 :58~65%,Al 2 O 3 :23~28%,Fe 2 O 3 :0.3% or less, TiO 2 :0.2% or less, K 2 O: 2~5%, Na 2 O: 2~6%, ZrO 2 :3~6%. For example, the chemical composition of the glaze includes: in terms of mass percentage, loss on burning: 2~5%, SiO 2 :58~65%,Al 2 O 3 :23~28%,Fe 2 O 3 :0.01~0.3%, TiO 2 :0.01~0.2%, K 2 O: 2~5%, Na 2 O: 2~6%, ZrO 2 :3~6%. As an example, the chemical composition of the glaze includes: in terms of mass percentage, loss on burning: 2~5%, SiO 2 :58~65%,Al 2 O 3 :23~28%,Fe 2 O 3 :0.01~0.3%, TiO 2 :0.01~0.2%, CaO: 0.01~0.5%, MgO: 0.01~0.5%, K 2 O: 2~5%, Na 2 O: 2~6%, ZrO 2 :3~6%.
[0041] In some embodiments, an additive and water are added to the mineral composition of the glaze, ball-milled evenly, and sieved to obtain a glaze slurry. The additives include but are not limited to sodium carboxymethyl cellulose and sodium tripolyphosphate. The glaze slurry can have a sieve residue of 0.5-0.8 wt % after passing through a 325 mesh sieve. When used, water can be added to the glaze slurry to obtain the final desired glaze specific gravity.
[0042] The glaze is applied by spraying. For example, a swing arm sprayer is used to spray the glaze. In some embodiments, the specific gravity of the glaze is 1.40-1.45 g / cm 3 , glaze application amount is 550~650g / m 2 .
[0043] The normal ink pattern is inkjet printed on the surface of the brick after the glaze is applied.
[0044] The glaze is applied to the surface of the tile blank after the ordinary ink pattern is printed by inkjet. At the location where the fine-carved ink is printed, the applied glaze is repelled by the fine-carved ink to form a concave texture, thereby exposing the ceramic blank. Therefore, at the location with the fine-carved ink pattern, the glaze can directly contact the light-transmitting blank. Since the high-temperature viscosity of the glaze is low, it can form a liquid phase earlier during high-temperature firing and react with the blank, so that the light-transmitting blank at the peeling position forms more glass phase, thereby increasing the light transmittance of this area.
[0045] The expansion coefficient of the transparent body of the high alkaline earth metal flux system mentioned above is relatively low. In order to match it, the present invention also designs a high-aluminum polishing glaze. The mineral composition of the polishing glaze includes: in terms of mass percentage, 10-15% potassium feldspar, 5-10% kaolin, 5-10% quartz, 5-10% calcined kaolin, 20-30% high-calcium high-aluminum frit, 10-15% burned talc, 15-20% wollastonite, and 3-6% zinc oxide.
[0046] The chemical composition of the high calcium and high aluminum frit includes: SiO 2 :40~45%,Al 2 O 3 : 20~30%, CaO: 10~15%, MgO: 1~5%, K 2 O: 1~5%, Na 2 O: 1-5%. Preferably, the high calcium and high aluminum frit of the glaze polishing has the same chemical composition as the high calcium and high aluminum frit of the light-transmitting body.
[0047] In some embodiments, the chemical composition of the glaze includes: by mass percentage, loss on burning: 1-5%, SiO 2 :50~55%,Al 2 O 3 :15~20%,Fe 2 O3 :0.3% or less, TiO 2 : 0.2% or less, CaO: 10~15%, MgO: 5~10%, K 2 O: 1~5%, Na 2 O: 1-5%, ZnO: 3-6%. For example, the chemical composition of the polishing glaze includes: in terms of mass percentage, loss on burning: 1-5%, SiO 2 :50~55%,Al 2 O 3 :15~20%,Fe 2 O 3 :0.01~0.3%, TiO 2 :0.01~0.2%, CaO: 10~15%, MgO: 5~10%, K 2 O: 1~5%, Na 2 O: 1~5%, ZnO: 3~6%.
[0048] In some embodiments, an additive and water are added to the mineral composition of the polishing glaze, ball-milled evenly, and sieved to obtain a polishing glaze slurry. The additives include but are not limited to sodium carboxymethyl cellulose and sodium tripolyphosphate. The residue of the polishing glaze slurry after passing through a 325-mesh sieve can be 0.5-0.8wt%. When used, water can be added to the polishing glaze slurry to obtain the final desired polishing specific gravity.
[0049] The glaze is sprayed by a swing arm glaze spraying machine. The specific gravity of the glaze is 1.50-1.55 g / cm 3 , glaze application amount is 500~550g / m 2 .
[0050] The glazed body is dried at high temperature.
[0051] Firing. It can be fired quickly in a roller kiln. For example, the firing temperature is 1180~1220℃ and the firing cycle is 60~80 minutes.
[0052] The overall texture of the positioned light-transmitting ceramic plate obtained by the present invention is moist and transparent. As mentioned above, the applied fine carving ink peels off the glaze, and the polishing glaze is in direct contact with the light-transmitting blank. Since the high-temperature viscosity of the polishing glaze is low, the liquid phase can be formed earlier during high-temperature firing to react with the blank, so that the blank at the peeling position is sintered more fully, forming more glass phases. The increase in glass phases also increases the light transmittance of the area. Under the irradiation of light, the area where the fine carving ink is printed is not covered by the glaze, and the glass phase content in the local position is higher, so more light can pass through, and thus it shows a stronger light transmission performance. After firing, when light passes through the ceramic plate, the light transmitted by the area printed with the fine carving ink is significantly stronger than that of other areas covered by the glaze, thereby achieving the high light transmittance effect of the positioned light-transmitting ceramic plate. A large visual contrast is formed in the local position, giving people a feeling closer to stone, enriching the decorative effect of the light-transmitting ceramic product. The light transmittance of the finished product after firing is detected using an LH-230 type densitometer. In some embodiments, the light transmittance of the transparent blank is 10-11.5, the light transmittance of the non-printed fine-carving ink area of the transparent ceramic plate is about 8.0-9.5, and the light transmittance of the printed fine-carving ink area of the transparent ceramic plate is 12-13.
[0053] The following examples are further listed to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0054] Example 1
[0055] The method for preparing the positioning light-transmitting ceramic plate comprises the following steps:
[0056] Step 1: Prepare a light-transmitting blank. The mineral composition of the light-transmitting blank includes: by mass percentage, 12% water-ground potassium sodium sand, 8% water-ground potassium feldspar, 6% burned talc, 14% wollastonite, 35% ultra-white kaolin, and 25% high-calcium high-aluminum frit. The mineral composition of the high-calcium high-aluminum frit includes: by mass percentage, SiO 2 :44.11%,Al 2 O 3 :29.31%, CaO: 14.53%, MgO: 4.74%, K 2 O: 3.55%, Na 2 O: 3.76%. A green body with a thickness of about 6.2 mm is obtained by pressing and then drying the green body at high temperature. The chemical composition of the light-transmitting green body includes: ignition loss: 4.83%, SiO 2:57.99%,Al 2 O 3 :20.79%,Fe 2 O 3 :0.02%,TiO 2 :0.01%, CaO: 8.94%, MgO: 3.36%, K 2 O: 2.23%, Na 2 O:1.83%.
[0057] Step 2: Use an inkjet printer to print a finely carved ink pattern on the surface of the translucent blank.
[0058] Step 3: Apply glaze to the surface of the body after the inkjet printing of the finely carved ink pattern. The mineral composition of the glaze includes: by mass percentage, 33% water-ground potassium sodium sand, 22% water-ground potassium feldspar, 11% calcined alumina, 6% zirconium silicate, and 28% ultra-white kaolin. The chemical composition of the glaze includes: by mass percentage, ignition loss: 3.2%, SiO 2 :60.31%,Al 2 O 3 :26.52%,Fe 2 O 3 :0.06%,TiO 2 :0.05%, K 2 O: 3.36%, Na 2 O: 2.47%, ZrO 2 :4.03%. The top glaze is sprayed by a swing arm glaze spraying machine. The specific gravity of the top glaze is 1.40g / cm 3 , glaze application amount is 550g / m 2 .
[0059] Step 4: Inkjet printing a normal ink pattern on the surface of the blank after applying the top glaze.
[0060] Step 5: Apply glaze to the surface of the blank after the ordinary ink pattern is printed by inkjet. The mineral composition of the glaze includes: by mass percentage, potassium feldspar 14%, kaolin 8%, quartz 6%, calcined kaolin 8%, high calcium high aluminum frit 28%, burned talc 14%, wollastonite 16%, zinc oxide 6%. The mineral composition of the high calcium high aluminum frit includes: by mass percentage, SiO 2 :44.11%,Al 2 O 3 :29.31%, CaO: 14.53%, MgO: 4.74%, K 2 O: 3.55%, Na 2 O: 3.76%. The chemical composition of the polishing glaze includes: in terms of mass percentage, loss on burning: 2.42%, SiO 2:54.11%,Al 2 O 3 :16.48%,Fe 2 O 3 :0.08%,TiO 2 :0.05%, CaO: 10.22%, MgO: 6.22%, K 2 O: 2.77%, Na 2 O: 1.65%, ZnO: 6%. The glaze is sprayed with a swing arm glaze sprayer. The specific gravity of the glaze is 1.50g / cm 3 , glaze application amount is 500g / m 2 .
[0061] Step 6: After the glazed bricks are dried at high temperature, they are quickly fired in a roller kiln. The firing temperature is 1180℃ and the firing cycle is 60 minutes.
[0062] Step 7: Polish, wax, grind the edges of the fired translucent ceramic plates, and pack them for storage.
[0063] Figure 2 This is a brick surface effect diagram of the positioned light-transmitting ceramic plate of Example 1. It can be seen that the area where the fine-carving ink is printed forms a line texture due to the repulsive effect of the oil-water system. Therefore, by using fine-carving ink combined with inkjet pattern texture, the pattern texture of the light-transmitting ceramic plate is closer to the stone effect.
[0064] The transmittance was measured using an LH-230 densitometer. The transmittance of the positioned transparent ceramic plate prepared in Example 1 was about 10 after firing, the transmittance of the unprinted fine-carving ink area of the positioned transparent ceramic plate was about 8.0, and the transmittance of the printed fine-carving ink area of the positioned transparent ceramic plate was about 12.
[0065] Example 2
[0066] The same as Example 1, except that the amount of glaze applied is 650 g / m 2 .
[0067] The light transmittance of the non-printed fine-carving ink area of the positioning light-transmitting ceramic plate prepared in Example 2 is about 7.0, which indicates that after increasing the amount of glaze applied, the light transmittance of the non-printed fine-carving ink area of the positioning light-transmitting ceramic plate is reduced; in contrast, the light transmittance of the printed fine-carving ink area of the positioning light-transmitting ceramic plate is 12, which is basically the same as that of Example 1, with no significant difference. This indicates that increasing the amount of glaze applied within a certain range has no significant effect on the light transmittance of the printed fine-carving ink area.
[0068] Comparative Example 1
[0069] The same as Example 1, the only difference is that the mineral composition of the light-transmitting blank includes: by mass percentage, 12% of water-ground potassium sodium sand, 8% of water-ground potassium feldspar, 6% of burned talc, 14% of wollastonite, 35% of ultra-white kaolin, and 25% of high-aluminum frit. The chemical composition of the high-aluminum frit includes: by mass percentage, SiO 2 :53.16%,Al 2 O 3 :28.51%, CaO: 0.56%, MgO: 2.38%, K 2 O: 6.59%, Na 2 O: 5.56%; ZnO: 3.24%. The chemical composition of the transparent body includes: in terms of mass percentage, burning loss: 4.82%, SiO 2 :60.27%,Al 2 O 3 :20.59%,Fe 2 O 3 :0.02%,TiO 2 :0.01%, CaO: 5.44%, MgO: 2.77%, K 2 O: 2.99%, Na 2 O: 2.28%; ZnO: 0.81%.
[0070] The light transmittance of the light-transmitting body of the ceramic plate prepared in Comparative Example 1 after firing is about 6. It can be seen that the light transmittance of the light-transmitting body of the ceramic plate prepared in Comparative Example 1 is relatively low.
[0071] Comparative Example 2
[0072] Solution 1: It is basically the same as Example 1, except that: different ordinary ink patterns are printed by inkjet; and the mineral composition of the glaze includes: by mass percentage, potassium feldspar 14%, kaolin 8%, quartz 6%, calcined kaolin 8%, high-alumina frit 28%, burned talc 14%, wollastonite 16%, zinc oxide 6%. The chemical composition of the high-alumina frit includes: by mass percentage, SiO 2 :53.16%,Al 2 O 3 :28.51%, CaO: 0.56%, MgO: 2.38%, K 2 O: 6.59%, Na 2 O: 5.56%; ZnO: 3.24%. The chemical composition of the polishing glaze includes: by mass percentage, the chemical composition of the polishing glaze includes: by mass percentage: loss on burning: 2.5%, SiO 2 :56.66%,Al 2 O 3 :16.26%,Fe 2 O3 :0.02%,TiO 2 :0.01%, CaO: 6.31%, MgO: 5.56%, K 2 O: 3.62%, Na 2 O: 2.15%, ZnO: 6.91%.
[0073] Option 2: Same as Option 1, except that the use of glaze is omitted.
[0074] Figure 3 This is the brick surface effect diagram of Example 2. Among them, Figure 3 The left part adopts the scheme 1 of applying glaze. Figure 3 The right part adopts scheme 2 without glazing. It can be seen that the glaze surface of the ceramic plate prepared in comparative example 2 appears opaque in the glazing area, and there is a clear boundary between the glazing area and the non-glazing area.
[0075] Comparative Example 3
[0076] The same as Example 1, the only difference is that: different ordinary ink patterns are printed by inkjet; and the mineral composition of the light-transmitting blank includes: by mass percentage, 12% water-ground potassium sodium sand, 8% water-ground potassium feldspar, 6% burned talc, 14% wollastonite, 35% ultra-white kaolin, and 25% low-calcium and low-aluminum frit. The chemical composition of the low-calcium and low-aluminum frit includes: by mass percentage, SiO 2 :59.8%,Al 2 O 3 :7.74%, CaO: 5.53%, MgO: 2.15%, K 2 O: 8.62%, Na 2 O: 10.35%, ZnO: 5.81%. The chemical composition of the transparent body includes: by mass percentage, burning loss: 5.47%, SiO 2 :61.77%,Al 2 O 3 :15.4%,Fe 2 O 3 :0.02%,TiO 2 :0.01%, CaO: 6.69%, MgO: 2.21%, K 2 O: 3.5%, Na 2 O: 3.48%, ZnO: 1.45%.
[0077] Figure 4 This is a brick surface effect diagram of comparative example 3. It can be seen that the light-transmitting green body prepared in comparative example 3 is in an over-burned state after firing, the green brick is easy to deform and crack, the strength is low, and it cannot be industrialized.
[0078] Comparative Example 4
[0079] The method is basically the same as Example 1, except that: different ordinary ink patterns are printed by inkjet; and the mineral composition of the glaze includes: by mass percentage, potassium feldspar 14%, kaolin 8%, quartz 6%, calcined kaolin 8%, low calcium and low aluminum frit 28%, burned talc 14%, wollastonite 16%, zinc oxide 6%. The chemical composition of the low calcium and low aluminum frit includes: by mass percentage, SiO 2 :59.8%,Al 2 O 3 :7.74%, CaO: 5.53%, MgO: 2.15%, K 2 O: 8.62%, Na 2 O: 10.35%, ZnO: 5.81%. The chemical composition of the polishing glaze includes: in terms of mass percentage, burning loss: 2.67%, SiO 2 :58.34%,Al 2 O 3 :10.45%,Fe 2 O 3 :0.02%,TiO 2 :0.01%, CaO: 7.70%, MgO: 5.49%, K 2 O: 4.19%, Na 2 O: 3.50%, ZnO: 7.63%.
[0080] Figure 5 This is a brick surface effect diagram of comparative example 4. It can be seen that the ceramic plate prepared in comparative example 4 has glaze cracks. This is because: in order to prepare a light-transmitting body with high light transmittance, the amount of alkaline earth metal flux in the light-transmitting body designed by the present invention is relatively large, resulting in a low expansion coefficient of the body, while the expansion coefficient of the polished glaze in this comparative example is relatively high. Since the expansion coefficient of the polished glaze does not match that of the body, the glaze layer cracks due to the tensile stress caused by the expansion of the light-transmitting body, affecting the decorative effect of the product.
[0081] Comparative Example 5
[0082] The same as Example 1, the only difference is that: different ordinary ink patterns are printed by inkjet; and the glaze amount of the polishing glaze is 800g / m 2 .
[0083] Figure 6This is the brick surface effect diagram of comparative example 5. It can be seen that the glaze surface of the ceramic plate prepared in comparative example 5 is concave, and the defects such as bubbles, pores, and volcanic holes on the glaze surface increase. This is because the amount of glaze applied is too high. During high-temperature firing, there is too much liquid phase in the area where the fine-carving ink is printed, and the body in this area is deformed due to over-firing, thus forming a concave. In addition, since the glaze layer is thick, it is not conducive to the gas discharge of the body during high-temperature firing, resulting in more bubbles remaining in the glaze layer, and more defects after polishing.
[0084] Comparative Example 6
[0085] It is basically the same as Example 1, except that the mineral composition of the glaze includes, by mass percentage, 30% water-ground potassium sodium sand, 15% water-ground potassium feldspar, 11% calcined alumina, 6% zirconium silicate, and 38% ultra-white kaolin.
[0086] The glaze surface of the ceramic plate prepared in Comparative Example 6 has many defects such as pinholes and volcanic holes. This is because the content of water-ground potassium feldspar in the surface glaze of this comparative example is reduced and the content of ultra-white kaolin is increased, resulting in a higher firing temperature of the surface glaze. Under the firing system of the present invention, when the light-transmitting body has been sintered and the polishing glaze has been melted, the surface glaze cannot be effectively sintered, resulting in a large amount of gas in the polishing glaze layer that has not been discharged, so that a large number of pores remain in the polishing glaze layer, thereby forming defects.
Claims
1. A method for preparing a positioning light-transmitting ceramic plate, characterized in that: The preparation method comprises the following steps: Inkjet printing a finely carved ink pattern on the surface of a light-transmitting blank; the mineral composition of the light-transmitting blank includes: by mass percentage, 10-15% of water-ground potassium-sodium sand, 5-10% of water-ground potassium feldspar, 5-10% of burned talc, 10-15% of wollastonite, 30-40% of ultra-white kaolin, and 20-30% of high-calcium and high-aluminum frit; wherein the chemical composition of the high-calcium and high-aluminum frit includes: by mass percentage, SiO2: 40-45%, Al2O3: 20-30%, CaO: 10-15%, MgO: 1-5%, K2O: 1-5%, and Na2O: 1-5%; Applying a glaze on the surface of the body after the inkjet printing of the finely carved ink pattern; the mineral composition of the glaze includes: in terms of mass percentage, 30-35% of water-ground potassium sodium sand, 20-25% of water-ground potassium feldspar, 10-15% of calcined alumina, 5-10% of zirconium silicate, and 25-30% of ultra-white kaolin; Inkjet printing a common ink pattern on the surface of the blank after the top glaze is applied; A glaze is applied to the surface of the blank after the ordinary ink pattern is inkjet printed; the mineral composition of the glaze includes: in mass percentage, potassium feldspar 10-15%, kaolin 5-10%, quartz 5-10%, calcined kaolin 5-10%, high calcium high aluminum frit 20-30%, burned talc 10-15%, wollastonite 15-20%, zinc oxide 3-6%; wherein the chemical composition of the high calcium high aluminum frit includes: in mass percentage, SiO2: 40-45%, Al2O3: 20-30%, CaO: 10-15%, MgO: 1-5%, K2O: 1-5%, Na2O: 1-5%; the specific gravity of the glaze is 1.50-1.55 g / cm 3 , glaze application amount is 500~550g / m 2 ; The green body with glaze applied is fired and polished to obtain the positioning light-transmitting ceramic plate.
2. The preparation method according to claim 1, characterized in that: The chemical composition of the light-transmitting blank includes, by mass percentage, loss on ignition: 2-5%, SiO2: 55-60%, Al2O3: 16-23%, Fe2O3: less than 0.5%, TiO2: less than 0.3%, CaO: 5-10%, MgO: 1-5%, K2O: 1-5%, and Na2O: 1-5%.
3. The preparation method according to claim 1, characterized in that: The chemical composition of the glaze includes, by mass percentage, loss on ignition: 2-5%, SiO2: 58-65%, Al2O3: 23-28%, Fe2O3: less than 0.3%, TiO2: less than 0.2%, K2O: 2-5%, Na2O: 2-6%, and ZrO2: 3-6%.
4. The preparation method according to claim 1, characterized in that: The glaze is applied by spraying; the specific gravity of the glaze is 1.40-1.45 g / cm 3 , glaze application amount is 550~650g / m 2 .
5. The preparation method according to claim 1, characterized in that: The chemical composition of the glaze includes, by mass percentage, loss on ignition: 1~5%, SiO2: 50~55%, Al2O3: 15~20%, Fe2O3: less than 0.3%, TiO2: less than 0.2%, CaO: 10~15%, MgO: 5~10%, K2O: 1~5%, Na2O: 1~5%, and ZnO: 3~6%.
6. The preparation method according to claim 1, characterized in that: The glaze is applied by spraying.
7. The preparation method according to claim 1, characterized in that: The firing temperature is 1180~1220℃ and the firing cycle is 60~80 minutes.
8. A positioning light-transmitting ceramic plate, characterized in that: The positioning light-transmitting ceramic plate is obtained according to the preparation method described in any one of claims 1 to 7.
Citation Information
Patent Citations
Translucent ceramic tile and preparation method thereof
CN107032772A
High-transparency ceramic rock plate with deep concave-convex textures and preparation method of high-transparency ceramic rock plate
CN114804824A
Ceramic rock plate with large-area transparent line texture and stone-imitating decorative effect and preparation method of ceramic rock plate
CN118420332A